ANALISIS PENYIMPANGAN MORFOSINTAKSIS DALAM UJARAN SISWA SMK : KAJIAN BERBASIS MORFEM DAN KATA - Ratna; R , Ummu Kalsum; Nensilianti; Amir, Johar (Jurnal Riset Guru Indonesia, 2025)
This study aims to describe the forms of morphosyntactic deviations that appear in the speech of students at SMK Negeri 5 Bulukumba, particularly at the morpheme and word levels. The background of this study is based on the phenomenon of students' spoken language use, which often does not conform to standard Indonesian language rules, influenced by regional languages, slang, and informal language habits in everyday life. This study uses a descriptive qualitative approach with data in the form of students' spoken language recorded during class discussions and interactions. The results of the study show several forms of morphological deviations, namely incorrect use of prefixes, suffixes, formation of double affixed words, omission of affixes, errors in reduplication, and errors in determining the basic form of words. These deviations indicate that students still have difficulty applying the rules of Indonesian morphology appropriately in formal communication contexts. These findings are expected to provide input for Indonesian language teachers in designing more effective learning strategies to improve students' oral language competence.